Mortality and Major Morbidity of Very-Low-Birth-Weight Infants in Germany 2008–2012: A Report Based on Administrative Data - Jeschke, Elke; Biermann, Alexandra; Günster, Christian; Böhler, Thomas; Heller, Günther; Hummler, Helmut D.; Bührer, Christoph, for the Routine Data-Based Quality Improvement Panel (Frontiers in Pediatrics, 2016)
Background: Expectant parents of very preterm infants, physicians and policy makers require estimates for chances of survival and survival without morbidity. Such estimates should derive from a large, reliable and contemporary data base of easily available items known at birth. Objective: To determine short-term outcome and risk factors in very low birth weight preterm infants based on administrative data Methods: Anonymized routine data sets transmitted from hospital administrations to statutory health insurance companies were used to assess survival and survival free of major morbidities in a large cohort of preterm infants in Germany. Results: After exclusion of infants with lethal malformations, there were 13,147 infants with a birth weight below 1,500 g admitted to neonatal care 2008-2012, of whom 1,432 infants (10.9%) died within 180 d. Estimated 180 d survival probabilities were 0.632 [95% confidence interval 0.583-0.677] for infants with 250-499 g birth weight, 0.817 [0.799-0.834] for 500-749 g, 0.931 [0.920-0.940] for 750-999 g, 0.973 [0.967-0.979] for 1,000-1,249 g and 0.985 [0.981-0.988] for 1,250-1,499 g. Estimated probabilities for survival without major morbidity (surgically treated intraventricular hemorrhage, necrotizing enterocolitis, intestinal perforation, or retinopathy) were 0.433 [0.384-0.481] (250-499 g), 0.622 [0.600-0.643] (500-749 g), 0.836 [0.821-0.849] (750-999 g), 0.938 [0.928-0.946] (1,000-1,249 g), and 0.969 [0.964-0.974] (1,250-1,499 g), respectively. Prediction of survival and survival without major morbidities was moderately improved by adding sex, small-for-gestational-age, and severe or moderate congenital malformation, increasing ROC areas under the curve from 0.839 [0.827-0.850] to 0.862 [0.852-0.874] (survival) and from 0.827 [0.822-0.842] to 0.852 [0.846-0.863] (survival without major morbidities), respectively. Conclusion: The present analysis encourages attempts to use administrative data to investigate the association between risk factors and outcome in preterm infants.